A review of fluid-structure interaction: blood flow in arteries - Zubeir Allum Saib; Farid Abed; Mergen H. Ghayesh; Marco Amabili (Biomedical Engineering Advances)
Over the past decade, Fluid-Structure Interaction studies related to blood vessels have been an active area of research, as they adequately capture the multiphysics of blood flow within the circulatory system. Despite the growing interest, only few state-of-the-art reviews have been published in the literature, each focusing individually on the coronary artery, carotid artery, aorta, heart valves and peripheral arteries. This systematic review assesses the current research and implications of Fluid-Structure Interaction implementation strategies in relation to human arteries. It is meant to comprehensively amalgamate research studies on an array of arteries coupled with cardiovascular complications such as atherosclerosis, plaque calcification, aneurysms, aortic dissections and valve dysfunction. It additionally covers computational finite element and finite volume solver demands, coupling schemes, inlet and outlet boundary conditions specifications, Newtonian and non-Newtonian blood rheological properties, laminar and turbulent flow types, as well as the modelling of the vessel wall’s hyperelastic and viscoelastic mechanical behavior. The research information is retrieved from the last ten years and summarized in a tabulated format, to help researchers in easily extracting useful information for future investigations and reviews.